The use of historical allusion in recent American and Arab fiction - Riyad Manqoush,; Noraini Md. Yusof,; Ruzy Suliza Hashim, (Pusat Pengajian Bahasa dan LInguistik, FSSK, UKM, 2011)
In this paper, we analyse John Updike’s Terrorist (2006) and Mohammad Ismail’s Desert of Death and Peace (2005) with the aim of examining the use of allusion in the depiction of 9/11 acts and the US occupation of Iraq. The comparison of the two novels, selected from two different literary traditions, enables us to explore American and Arab viewpoints of recent history. By appropriating the discussions of Gerard Genette, Michael Leddy, William Irwin, John Campbell and Allan Pasco on the use of allusion in literature, we argue that when authors allude to history in their works, they either employ allusion to affirm or oppose certain notions. In other words, there are two main strategies of allusion: affirmation and opposition. Updike alludes to history to affirm that Arab terrorists are the main enemies of the USA and also to oppose the actions of those terrorists who give themselves the right to kill civilians. In contrast, Ismail asserts that the Iraqi and American people are equally victims of super-power Jews. Therefore, he exposes an opposition to the US occupation of Iraq and the irrational reaction of the US to 9/11. Both novels implicitly utilise 9/11 and the US occupation of Iraq but each one employs these incidents according to the viewpoint and cultural background of its author. Hence, the different employment of history reveals contestations of worldviews which are symptomatic of the ideological clashes between the East and West.